PENAFSIRAN ABDULLAH BIN ABBAS TENTANG SURAH AL-IKHLAS DALAM KTAB TAFSȊR TANWȊR AL-MIQBÂS FI TAFSȊR IBN ‘ABBĀS - Irfaniyah, Alia (ojs.unsiq.ac.id, 2023)
This istudy idescribes ithe icapture iof isurah iAl-Ikhlas iaccording ito iibn iAbbas iin ithe ibook iof iTafsȋr iTanwȋr iAl-Miqbâs iMin iTafsȋr iIbn i‘Abbās iwhich ihas ibeen icompiled iby iFairȗzabâdi. iHe iis ia ischolar iwho iwas iborn iin i728 iin iKazrun i(Persi). iIn ithis istudy ithe iauthors iused ithe ilibrary iresearch imethod ior ilibrary iresearch ito iexplain ithe imethod iused iby iIbn i‘Abbās iin ihiding ior iexplaining isurah iAl-Ikhlas. iThis iexplanation ihas ibasically ibeen idiscussed iin iseveral iprevious istudies iand ialso iin iseveral ijournals isuch ias iHasan iAsyari's ijournal iwhich iexplains iTafsȋr iIbn i‘Abbās iand ialso iAhmad iNurul iet ial's iJurnal iwhich idiscusses iTafsȋr iSurah iAl-Fatihah. iTherefore, ithere iare idifferences iin ithe iprevious iresearch iand ithis iresearch iwhich idiscusses ithe iinterpretation iof iSurah iAl-Ikhlas iwhich iexplains ithe iOneness iof iAllah iAzza iwa iJalla.